Factors influencing individualized nursing care in acute medical and perioperative settings: A scoping review - Ramos, Ana (2024)
Individualized nursing care addresses the needs, experiences, behaviors, feelings, and perceptions of patients and families, but its implementation in clinical practice contexts remains challenging. This review aims to map the factors that interfere with the individualization of nursing care, in acute medical and perioperative settings. Scoping review was conducted according to the Joanna Briggs Institute guidelines. The MEDLINE, CINAHL, Cochrane, SciELO, Scientific Repository of Open Access, and LILACS databases were searched for publications from January 2017 up to March 2023. Of the 124 articles selected, 17 met the inclusion criteria. The individualization of nursing care is complex and shaped by multiple variables in the care environment, nursing, and patient characteristics. The institutional organization, the nurses’ expertise, and the patient’s attributes were identified as variables that interfere with the individualization of nursing care. Individualized nursing care is responsible for better quality of care and health outcomes. The identification of the variables that affect individualized care contributes to planning programs to improve individualization, during hospitalization and the discharge.